Pemoderasi Pengaruh Kompetensi Aparatur Desa Dan Sistem Pengendalian Internal Pada Pencegahan Fraud - Dewi, Luh Ayu Marsita; Damayanthi, I Gusti Ayu Eka (E-Jurnal Akuntansi; Vol 26 No 3 (2019)DO - 10.24843/EJA.2019.v26.i03.p26, 2019)
The purpose of this study is to examine the influence of village apparatus competencies and internal control systems on prevention of fraud which are moderated by internal locus of control. This research was conducted in all village offices of the City of Denpasar. The number of samples taken was 81 village officials, with a saturated sample method. Data collection is done by questionnaires and interviews. The analysis technique used is the Moderate Regression Analysis (MRA). Based on the results of the analysis it was found that internal locus of control was able to strengthen the influence of apparatus competencies and internal control systems on fraud prevention in managing village funds. So it is recommended that village governments always consider the self-control of village officials in managing village finances. Keywords : Fraud, competence, internal control system, internal locus of control